A Cross-Sectional Study of Lower Back Pain in Women Fish Processors - Ana Islamiyah Syamila; Isa Marufi; Kurnia Ardiansyah Akbar (Universitas Airlangga, 2026)
Introduction: Introduction: Coastal women have a large role in fishing households by carrying out fish processing work. The facts show that fish processing work carried out without paying attention to ergonomic factors is vulnerable to LBP complaints. This study aims to analyze LBP complaints among women processing fish. Methods: This type of research is analytical observational research with a cross-sectional design. Data were collected through structured questionnaires and face-to-face interviews with 110 respondents to collect social demographics, job factors, history of LBP, and LBP complaints. Other primary data is measuring workers' nutritional status, repetitive movements, and physical workload. A logistic regression test was carried out to analyze the relationship between each independent variable and LBP complaints. Results: Occupational factors related to LBP were slipping on slippery floors (aOR = 6.62; 95% CI: 1.88, 23.27), squatting (aOR = 0.62; 95% CI: 0.43, 0.89), static posture (aOR = 1.22; 95% CI: 1.02, 1.47), and repetitive movements (aOR = 0.78; 95% CI: 0.63, 0.97). The history of LBP that significantly increased LBP was the frequency of occasional pain (aOR = 6.27; 95% CI: 1.47, 26.62), and absenteeism (ORs = 2.80; 95% CI: 1.10, 7.07). Conclusion: There is a relationship between age, years of work, having another job, incidents of slipping while working, squatting, static postures, repetitive movements, frequency of pain, and absenteeism with complaints of LBP. LBP experienced by women fish processors is a serious problem that requires ergonomic evaluation and work area design control. Occupational factors significantly worsen the occurrence of LBP.